2008
DOI: 10.1063/1.2948938
|View full text |Cite
|
Sign up to set email alerts
|

Spectral investigation of carrier recombination processes in ZnO nanorods at high temperatures

Abstract: The mechanism of near-band-edge (NBE) emission from crystalline ZnO (c-ZnO) nanorods grown on c-Si by a catalyst-assisted vapor-liquid-solid method has been investigated by performing temperature-, power-, and time-dependent photoluminescence (PL) measurements at a temperature (T) range of 143–503K. In contrast to previous reports, we find that the NBE PL is primarily associated with free exciton emission, whereas the contribution of band-to-band and free-to-bound radiative recombinations remains negligible up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 26 publications
3
7
0
Order By: Relevance
“…Actually, the excitation power-dependent redshi has been investigated in detail. 32,33 Yang and Li proposed that laser-induced local heating effect is the origin of the phenomenon and the established theoretical model agrees well with the experiment results. 34 However, Rao et al pointed out that the heating effect alone cannot explain the observed shi in the PL with the variation in excitation intensity, based on the fact that some samples were free of spectrum shi and the same phenomenon was even found in a liquid nitrogen environment.…”
Section: Resultssupporting
confidence: 68%
“…Actually, the excitation power-dependent redshi has been investigated in detail. 32,33 Yang and Li proposed that laser-induced local heating effect is the origin of the phenomenon and the established theoretical model agrees well with the experiment results. 34 However, Rao et al pointed out that the heating effect alone cannot explain the observed shi in the PL with the variation in excitation intensity, based on the fact that some samples were free of spectrum shi and the same phenomenon was even found in a liquid nitrogen environment.…”
Section: Resultssupporting
confidence: 68%
“…For the individual nanorods the CL maximum shifts to 377 (3.29 eV) nm for the wide nanorod and to 372 nm (3.33 eV) for the thin nanorod. The diameter of nanorods studied is too large for the quantization effects therefore the blue luminescence shift should be explained by other reasons, for example, by the self-absorption of the free exciton emission in the thicker nanorods [7]. Investigations of low energy electron irradiation effects on the CL of ZnO nanorods showed that the e-beam exposure led to the CL intensity increasing with the exposure dose increase without noticeable change of emission spectrum and this increase could reach one order of magnitude.…”
Section: Resultsmentioning
confidence: 98%
“…A strong relative quenching of the defect PL has been also observed to start at T ~ 400 K and attributed to a competing effect of a thermally-induced ionization of deep defect states, which has been also in part discussed in [14] by us; however, more detailed investigation of this behavior will be needed and postponed until future work.…”
mentioning
confidence: 79%